Control of multi-machine using adaptive fuzzy - Bouchiba Bousmaha; Hazzab Abdeldjebar; Glaoui Hachemi; Med-Karim Fellah; Bousserhane Ismaïl Khalil; Sicard Pierre (Serbian Journal of Electrical Engineering, 2011)
An indirect Adaptive fuzzy excitation control (IAFLC) of power systems based on multi-input-multi-output linearization technique is developed in this paper. The power system considered in this paper consists of two generators and infinite bus connected through a network of transformers and transmission lines. The fuzzy controller is constructed from fuzzy feedback linearization controller whose parameters are adjusted indirectly from the estimates of plant parameters. The adaptation law adjusts the controller parameters on-line so that the plant output tracks the reference model output. Simulation results shown that the proposed controller IAFLC, compared with a controller based on tradition linearization technique can enhance the transient stability of the power system.